Linagliptin Efficacy on Hyperglycemia, Oxidative Stress, and Inflammation in Gestational Diabetes Mellitus - Ajao, Folasade Omobolanle; Yusuf, Oluwatobi Olayiwola; Balogun, Damilola Ayodeji; Iyedupe, Marcus Olaoye; Adesola, Mariam Olayinka; Egunjobi, George Adetomiwa (Clinical Journal of Obstetrics and Gynecology, 2024)
Background: Linagliptin is an anti-diabetic drug that claims no adverse effects and treatment of gestational diabetes mellitus (GDM) demands a safe anti-diabetic medication. Therefore, this study investigates the anti-diabetic efficacy of linagliptin in an induced GDM. Materials and methods: Thirty-two matured female rats (100 - 200 g) were utilized. Sixteen non-pregnant/diabetic animals were fed with a normal diet and sixteen rats were fed with a high-fat (HFD), mated at the estrous stage in 2:1, and pregnancy was confirmed with a spermatozoa in a vaginal smear. The pregnant rats were intraperitoneally injected with a single dose (30 mg/kgb. wt) of streptozotocin (STZ) to induce GDM. The animals were grouped into 4 groups, 8 rats/groups. Group I: control; Group II: control + 10 mg/kgb.wt linagliptin; Group III: GDM; Group IV: GDM + 10 mg/kgb.wt linagliptin. The animals were sacrificed after 14 days of treatment. Blood samples were collected for biochemical parameters. Results: Fasting blood glucose (FBG) insulin, glycated hemoglobin (HbA1c), total cholesterol (TC), triglyceride (TG), low-density lipoprotein-cholesterol (LDL-C), malondialdehyde (MDA), interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-alpha (TNF-α) levels significant (p < 0.05) elevated in GDM rats, with significant reduction in high-density lipoprotein-cholesterol (HDL-C), catalase (CAT), superoxide dismutase (SOD) and reduced glutathione (GSH). Linagliptin administration significantly (p < 0.05) decreased the FBG, insulin, HbA1c, TC, TG, LDL-C, MDA, IL-6, IL-1β, and TNF-α and ameliorates the HDL-C, CAT, SOD, and GSH levels significantly. Conclusion: Linagliptin remarkably showed anti-hyperglycemic, anti-oxidative, and anti-inflammatory properties. Linagliptin could be a promising drug for hyperglycemia treatment during gestation.